A satisfação do usuário do serviço de tratamento fora de domicílio do município de Sant’ana do Livramento - (:unkn) unknown (Universidade Federal do Pampa, 2014)
Health is a right guaranteed in the Constitution of our country, and the State provides conditions for this right is realized for all citizens. The present study aimed to identify the degree of perceived user satisfaction Treatment Outside the Household service provided by the Municipal Health Santana of Deliverance. This research is justified by the absence of assessments of user satisfaction of the municipal public health services. The method used for data collection was a structured questionnaire and documentary research. This study is featured as a case study where the method used was a quantitative-qualitative research due to the data collected through the questionnaire provide a subjective perception through the content analysis of the responses and make a percentage analysis and mean degree of satisfaction of respondents, where it was found that this service is used predominantly by women with incomplete secondary school and low-income level, thus emphasizing the importance of the public manager to make yourself worth of instruments to assess the quality and service in the public health service in the municipality.
Keywords: Public management: Brazil: Rio Grande do Sul: Santana do Livramento; Public administration: models; Customer satisfaction; Public health: home medical treatment; Treatment out of domicile; CNPQ::CIENCIAS SOCIAIS APLICADAS; Gestão pública: Brasil: Rio Grande do Sul: Santana do Livramento; Administração pública: modelos; Satisfação do cliente; Saúde pública: tratamento médico domiciliar; Tratamento Fora de Domicílio - TFD